Show Me the Money: Industry Payments to American Association of Endocrine Surgeons Members - McMullin, Jessica Liu; Wang, Rongzhi; Gillis, Andrea; Zmijewski, Polina; Lindeman, Brenessa; Fazendin, Jessica; Chen, Herbert (The Journal of surgical research, 2024)
The Open Payments Program (OPP) was created through the Physician Payments Sunshine Act to disclose transactions between physicians and industry. Various surgical subspecialties have evaluated trends in OPP; however, this has not been looked at among endocrine surgeons. Our objective was to describe OPP trends among members of the American Association of Endocrine Surgeons (AAES). A list of members from the AAES was compiled using membership information from the AAES annual meetings. These surgeons were queried in the OPP database from 2014 to 2020. Payments were classified as general payments and research payments. From 2014 to 2020, 417 surgeons in the AAES received a total of $5,870,113 in general payments with an annual range from $542,945 to $1,010,564. The median payment was $701 (interquartile range [IQR] $145-$4641) over all years. The top 10th percentile received >85% of the payments ($5,058,207) with the median payment in this decile being $37,535.06 (IQR $26,599-$112,380). The most common category for payments was food and beverage (63.5%) followed by travel and lodging (22.6%) and consulting fees (4.1%). Regarding research payments, 30 surgeons received $9,522,374 with a median payment of $45,635.68 (IQR $12,050-$158,863). Members of the AAES received a total of $15,392,487 in money from industry between 2014 and 2020 in general and research payments demonstrating that the industry relationship is substantial. The majority of these payments were given to only a small portion of surgeons. The transparency created by OPP is critical for endocrine surgeons to prevent public misconceptions and identify the potential for any conflicts of interest.